Intertekstualność jako forma dialogu międzykulturowego - Muszyńska, Anna (Przekłady Literatur Słowiańskich, 2011)
Intertextuality as a way of cultural dialogue The artistic texts which as a part of the intertextuality phenomena refer to other texts, known only in the native literary tradition and culture of the original text, present an enormous challenge for the translator ( in this article the deliberations on this subject are illustrated by the work of Bolesław Leśmian titled Urszula Kochanowska in a Slovenian translation of Tone Pretnar). The intertexual elements go into a dialogue with a literary translation and a target culture because in a foreign context they function differently. However, they always have enriching value (at least from the cognitive perspective).